The Egyptian Journal of Remote Sensing and Space Sciences – Elsevier - (:unkn) unknown (My University, 2026)
The Egyptian Journal of Remote Sensing and Space Sciences (EJRS) covers all aspects of Remote Sensing, Geographic Information Systems and the development of Space Technologies and Applications. The objective of EJRS is to publish on the development of remote sensing technology and its applications for optimal planning, sustainable development and the protection of the environmental resources.